(untitled) - Redaktion: Dr. Patricia Schneider (V.i.S.d.P.), Chefredakteurin, Institut für Friedensforschung und Sicherheitspolitik an der Universität Hamburg; Susanne Bund, Institut für Friedensforschung und Sicherheitspolitik an der Universität Hamburg; FKpt. Prof. Dr. Frank Reininghaus, Institut für Friedensforschung und Sicherheitspolitik an der Universität Hamburg; Dr. Sybille Reinke de Buitrago, Institut für Friedensforschung und Sicherheitspolitik an der Universität Hamburg; Dr. Tim René Salomon, Institut für Friedensforschung und Sicherheitspolitik an der Universität Hamburg; Zentrum für Sicherheit und Recht an der Bucerius Law School, Hamburg (S&F Sicherheit und Frieden, 2009)
S+F (Securit y and Peace) is the leading German journal for peace research and security policy. S+F aims to serve as a forum linking civil society and the armed forces in the areas of science and politics comprising of research analysis, insider reports and opinion pieces. Decisions on publication are made on the basis of the contribution made by a text to national and international discussions on peace and security issues; from scientific aspects of arms control, to questions of nation-building in post-war societies. Every issue of S+F is focussed on a particular theme. In addition to contributions devoted to the central theme, texts addressing general aspects of peace and security research are also published. Contributors can choose whether to have the text evaluated by the editorial team or by way of an external evaluation process (double-blind peer-review). Articles of the journal S+F are entered in various national and international bibliographic databases. Among them are Online Contents OLC-SSG Politikwissenschaft und Friedensforschung (Political Science and Peace Research), PAIS (Public Affairs Information Service) International Database, Worldwide Political Science Abstracts and World Affairs Online (by the Fachinformationsverbund Internationale Beziehungen und Länderkunde FIV / The German Information Network International Relations and Area Studies) (see also www.ireon-portal.de). Website: www.sicherheit-und-frieden.nomos.de